Medical problems of Sri lankan pilgrims during pilgrimage to Mecca, Saudi Arabia - Sheriff, M.H.R.; Iqbal, Zanoon (My University, 1985)
The annual pilgrimage by Muslims to the Holy Cities of Mecca And Medina in Saudi Arabia is an international event and is obligatory on every Muslim all over the world if he can afford and is of good physical and mental health, at least once during his or her lifetime. The department of Muslim affairs in Colombo has organized the pilgrimage for Sri Lanka Muslims since 1981 and the first author has accompanied the pilgrims from Sri Lanka in 1981, 1983 and 1984 to attend to their medical needs as the official physician. In 1984, the Sri Lanka Hajj medical mission (2 doctors, 1 volunteer nurse, 1 attendant) has accompanied the pilgrims who performed hajj in the Sri Lankan camps. These included Sri Lankans working in Middle Eastern countries. The total pilgrims were estimated at two million. The paper describes the different conditions which the pilgrims unused to the crowded, hot, dry, dusty environment living in temporary tents in the desert during the 3 week pilgrimage, have to face with and the spectrum of conditions they presented with to the medical tent. During the 1984 Hajj, there were 801 recorded consultations (approximately 40per day) and 5 deaths over 25 days of the pilgrimage. The 5 deaths were due to acute myocardial infarction (2) cerebrovascular accident (1), heat stroke (1) and severe emphysema.